PENGEMBANGAN BUKU AJAR BERBASIS SCIENTIFIC APPROACH PADA MATA PELAJARAN AKUNTANSI PERBANKAN KELAS XI PERBANKAN DAN KEUANGAN MIKRO SMK NEGERI 1 KALITENGAH LAMONGAN - Vivi Dwi Triska; Rochmawati Rochmawati (FKIP Unswagati, 2021)
AbstractThe application of the Revised K13 requires learning devices that act as learning resources, one of which is textbooks. In class XI Banking and Microfinance in the banking accounting subject, there are no textbooks in accordance with the applicable curriculum. The purpose of this development research is to develop and create products in the form of textbooks based on the banking accounting scientific approach for class XI students of Banking and Microfinance at SMK Negeri 1 Kalitengah Lamongan based on the 2014 BSNP standards. In this study also tested the validity of the feasibility of textbooks by students expert. The model used in this development research is the 4D model which includes the stages of define, design, develop, and disseminate. However, this research did not reach the dissemination stage, due to limited time and cost. The results showed the feasibility of presenting material, language, and graphics with a percentage of each component, namely 93.56%, 92.37%, and 98.1%. Therefore, the Banking Accounting textbook is very feasible to use.Key Words: Textbooks, Scientific Approach, Banking Accounting